Motor Imagery and Pain Processing in Patients With Entrapment Neuropathies: A Cross-sectional Study - Matesanz-García, Luis; Fernández-Chamorro, Laura; Rubio-Vallejo, Alberto; Cecilia-López, David; Cuenca-Martínez, Ferran; Di-Bonaventura, Silvia; Fernández-Carnero, Josué (The Clinical journal of pain, 2023)
(1) To assess the ability to generate both kinesthetic and visual motor imagery in participants with carpal tunnel syndrome (CTS), compared with asymptomatic participants. (2) To assess the influence of psychophysiological and functional variables in the motor imagery process. Twenty patients with unilateral CTS and 18 pain-free individuals were recruited. An observational case-control study with a nonprobability sample was conducted to assess visual and kinesthetic movement imagery ability and psychophysiological variables in patients with CTS compared with asymptomatic participants in a control group. The trial was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology statement. CTS patients have more difficulties in generating visual motor images compared with asymptomatic individuals ( t =-2.099; P <0.05; d=0.70). They need more time to complete the mental tasks (visual t =-2.424; P <0.05 and kinesthetic t =-2.200; P <0.05). A negative correlation was found between the ability to imagine and functional deficits ( r =-0.569; P =0.021) for the kinesthetic subscale and temporal summation ( r =-0.515; P <0.5). A positive correlation was found between pain pressure threshold homolateral (homolateral) and time to generate the visual mental images ( r =0.537; P <0.05). CTS patients have greater difficulty generating motor images than asymptomatic individuals. Patients also spend more time during mental tasks. CTS patients present a relationship between temporal summation and the capacity to generate kinesthetic images. In addition, the CST patients presented a correlation between chronometry mental tasking and mechanical hyperalgesia.